2022
DOI: 10.1021/acsami.2c05654
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Carrier Separation in Visible-Light-Responsive Polyoxometalate-Based Metal–Organic Frameworks for Highly Efficient Oxidative Coupling of Amines

Abstract: Photocatalytic technology is widely studied, while it comes with drawbacks such as low sunlight utilization efficiency and high carrier recombination rates. Herein, for the first time, we present two crystalline polyoxometalate (POM)-based metal−organic frameworks (POMOFs), {[Cd(DMF) 2 Ru(bpy) through assembling the photosensitizer [Ru-(bpy) 2 (H 2 dcbpy)]Cl 2 and POMs into a single framework. The assembly not only enhances light absorption in the visible light regime but also improves carrier separation effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 65 publications
1
47
0
Order By: Relevance
“…Given the fact that the performance of a photocatalytic process relies on multiple collective factors including excitation wavelength, bulk diffusion, and surface transfer of photogenerated charge carriers, the charge separation and carrier migration processes of CR-SiW 12 and SiW 12 were investigated. As shown in Figure c, the CR-SiW 12 photoelectrode displays a higher photocurrent response compared with SiW 12 under intermittently visible light illumination, showing its better carrier separation efficiency . Meanwhile, the Nyquist plot indicated that CR-SiW 12 has a smaller arc radius than SiW 12 (Figure d), denoting its lower charge-transfer resistance .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Given the fact that the performance of a photocatalytic process relies on multiple collective factors including excitation wavelength, bulk diffusion, and surface transfer of photogenerated charge carriers, the charge separation and carrier migration processes of CR-SiW 12 and SiW 12 were investigated. As shown in Figure c, the CR-SiW 12 photoelectrode displays a higher photocurrent response compared with SiW 12 under intermittently visible light illumination, showing its better carrier separation efficiency . Meanwhile, the Nyquist plot indicated that CR-SiW 12 has a smaller arc radius than SiW 12 (Figure d), denoting its lower charge-transfer resistance .…”
Section: Resultsmentioning
confidence: 98%
“…In particular, the O 2 /aldehyde system known as the Mukaiyama method is very attractive in industrial production owing to its advantages of safety, green nonpollution, and high yield. , Recently, researchers have reported a lot of excellent work to develop a low-cost B–V oxidation process based on the Mukaiyama method. Nevertheless, conventional thermo-catalytic technologies often require high-temperature energy to trigger the catalytic reaction, which still suffers from the issues of high energy consumption and advanced facility requirements, thereby limiting the scalability of the process. Recent studies show that photocatalytic technology has become a research hotspot in the field of organic synthesis by utilizing economical solar energy as the driving force, with advantages including mild reaction conditions, high selectivity, and environmental friendliness. Consequently, the development of the photoinduced B–V oxidation process based on the Mukaiyama method is of great research significance.…”
Section: Introductionmentioning
confidence: 99%
“…As a category of newly emerged crystalline porous materials, metal–organic frameworks (MOFs) have been proposed as potential photocatalysts for selective oxidation reactions because of their unique excitation and charge transition mechanisms. Recently, some MOFs have been reported for the photocatalytic aerobic oxidative coupling of amines, but the reaction kinetics caused by the low efficiency of the photogenerated charge separation still needs to be greatly improved to meet the potential practical application requirements. There are many reported strategies in optimizing the photocatalytic activities of MOFs, in which the electron/energy transfer representing the central science of natural photosynthesis is widely introduced. Assembling electron donor and acceptor chromophores in a single MOF can realize the photoinduced electron transfer (PET). However, due to the construction of MOFs, in which donor and acceptor chromophores with similar geometry and connectivity both as ligands, is a great challenge, most of the current reported MOFs with the PET process are organized via using either the donor or the acceptor as the guest molecule, which damages the porosities of MOFs and severely limits their applications in photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there have been several reports on the construction of hybrid POMs to improve visible-light absorption by introducing appropriate organic groups into POMs to achieve better photocatalytic performance. , [Ru­(bpy) 3 ] 2+ (bpy = 2,2′-bipyridine) and its derivatives are famous photosensitizers, which have good photoredox and light-harvesting properties . Recently, our group combined [Ru­(bpy) 3 ] 2+ derivatives and POMs into a single framework to make POM-based metal–organic framework (POMOF) materials . The introduction of [Ru­(bpy) 3 ] 2+ derivatives expanded the light absorption range of POMOFs, and the synergistic effect of [Ru­(bpy) 3 ] 2+ derivatives and POMs enhanced the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…29 Recently, our group combined [Ru(bpy) 3 ] 2+ derivatives and POMs into a single framework to make POM-based metal−organic framework (POMOF) materials. 30 The introduction of [Ru(bpy General Procedure for Photocatalytic Selective Oxidation of Sulfides. The photocatalytic reaction was carried out on a WATTCAS Parallel Light Reactor (WP-TEC-1020HSL) (Figure S2).…”
Section: ■ Introductionmentioning
confidence: 99%